Energy aware software evolution for Wireless Sensor Networks - Hughes, Danny; Cañete, Eduardo; Daniels, Wilfried; Gowri Sankar, R.; Meneghello, James; Matthys, Nelson; Maerien, Jef; Michiels, Sam; Huygens, Christophe; Joosen, Wouter; Wijnants, Maarten; Lamotte, Wim; et al. (2013 IEEE 14th International Symposium on a World of Wireless, Mobile and Multimedia Networks (WoWMoM), 2013)
Wireless Sensor Networks (WSNs) are subject to high levels of dynamism arising from changing environmental conditions and application requirements. Reconfiguration allows software functionality to be optimized for current environmental conditions and supports software evolution to meet variable application requirements. Contemporary software modularization approaches for WSNs allow for software evolution at various granularities; from monolithic re-flashing of OS and application functionality, through replacement of complete applications, to the reconfiguration of individual software components. As the nodes that compose a WSN must typically operate for long periods on a single battery charge, estimating the energy cost of software evolution is critical. This paper contributes a generic model for calculating the energy cost of the reconfiguration in WSN. We have embedded this model in the LooCI middleware, resulting in the first energy aware reconfigurable component model for sensor networks. We evaluate our approach using two real-world WSN applications and find that (i.) our model accurately predicts the energy cost of reconfiguration and (ii.) component-based reconfiguration has a high initial cost, but provides energy savings during software evolution.